Efektivitas Penggunaan Media Pembelajaran Berbasis Multiple Representasi Dalam Pembelajaran Kimia: Tinjauan Literatur - Akbar, Jakub Saddam; Djakariah (Journal of Chemistry Sciences and Education, 2025)
Chemistry learning requires students to develop the ability to comprehend complex and abstract concepts through the interconnection of macroscopic, microscopic, and symbolic levels of representation. However, numerous studies have revealed that students often struggle to integrate these three levels, resulting in a fragmented and mechanical understanding of chemical concepts. One effective pedagogical approach to address this issue is the use of multiple representation-based instructional media, which enables the presentation of chemical concepts through various interconnected forms of visualization and symbolization. This study aims to examine the effectiveness of multiple representation-based learning media in enhancing students’ conceptual understanding in chemistry education. The research employed a systematic literature review (SLR) method by collecting and analyzing scientific articles from Google Scholar, SINTA, and ERIC databases using the keywords “multiple representation” and “chemistry learning.” Based on the screening process, 15 relevant articles published between 2018 and 2023 were selected for in-depth analysis. The selected studies were reviewed descriptively and comparatively, focusing on research outcomes, methodologies, and their contributions to improving the quality of chemistry learning. The review findings indicate that the use of multiple representation-based media—such as animations, augmented reality (AR), electronic modules, and interactive multimedia—has proven effective in improving conceptual understanding, critical thinking skills, creativity, and students’ learning motivation. Moreover, such media facilitate diverse learning styles and reduce misconceptions regarding chemical phenomena. In conclusion, multiple representation-based instructional media demonstrate high effectiveness in fostering deep and contextual understanding of chemistry concepts and hold great potential as an innovative learning strategy for 21st-century education.